Scratch-resistant PE protective film and preparation method thereof

Through the blending of LLDPE and HDPE and the use of modified composite fillers, the problem of degradation of scratch resistance of polymer materials is solved, the mechanical properties and scratch resistance of PE protective film are improved, and the long-lasting scratch resistance effect is achieved. Suitable for industrial production.

CN119119626AInactive Publication Date: 2024-12-13HUICANG NEW MATERIALS (SUZHOU) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311369003.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The scratch resistance of existing polymer materials is easily degraded during use, and traditional modification methods have a great negative impact on the mechanical properties of the materials, making it difficult to improve the scratch resistance of the long-lasting.

Method used

Using the blending of LLDPE and HDPE, and adding modified composite filler and modified carbon fiber powder, the compatibility of inorganic particles and polymer materials can be improved by modifying the mechanical properties and scratch resistance of PE protective film. The preparation method includes The modification of talc powder, silicon carbide, the reaction of carboxylated silica and modified silica, combined with the thiol-ene reaction of trimethylolpropane tri(3-mercaptopropionate) ester to form chemical bonds and interface binding forces .

Benefits of technology

It significantly improves the scratch resistance and mechanical properties of the PE protective film, achieves the improvement of long-lasting scratch resistance, and simplifies the preparation process and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004505171610000151
    Figure BDA0004505171610000151
Patent Text Reader

Abstract

The scratch-resistant PE protective film is prepared from the following raw materials in parts by weight: 90 to 100 parts of LLDPE (Linear Low Density Polyethylene), 10 to 20 parts of HDPE (High-Density Polyethylene), 4 to 8 parts of TPU (Thermoplastic Polyurethane), 10 to 20 parts of modified composite filler, 2 to 6 parts of modified carbon fiber powder, 0.1 to 0.3 part of an anti-blocking agent, 0.2 to 0.4 part of an ultraviolet absorbent and 0.5 to 1 part of a heat stabilizer. According to the scratch-resistant PE protective film, inorganic particles are added for filling, other wear-resistant high-molecular materials are introduced, under the synergistic effect of all the components, the scratch resistance of the PE protective film is remarkably improved, meanwhile, the inorganic particles are modified, the compatibility between the inorganic particles and high-molecular polymers is improved, and the scratch resistance of the PE protective film is improved. Therefore, the PE protective film has good mechanical properties and durable scratch resistance, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a scratch-resistant PE protective film and a preparation method thereof. Background Art

[0002] With the widespread application of polymer materials in packaging, automobiles, and architectural decoration, the requirements for their surface quality are getting higher and higher. During transportation, placement, assembly, and use, the surface of the material is easily scratched by hard or sharp objects, causing cracks or brittle damage on the surface, thereby reducing the aesthetics of the product; at the same time, scratches on the surface of the product are also prone to cause stress concentration, reducing the performance of the material, and even causing product failure.

[0003] At present, the methods for modifying the scratch resistance of polymer materials mainly include adding scratch resistance agents, filling reinforcement and blending modification. Among them, the use of scratch modifiers can improve the smoothness of polymer materials, thereby increasing the scratch resistance of polymer materials. The modifiers usually added are amides and silicones, which can automatically form a waxy lubricating layer when the polymer is cooled, reducing the friction in the friction and scratching behavior. However, amide small molecule additives can migrate from the inside of the material to the surface during the cooling process of the polymer, and may degrade and precipitate under the action of light and heat, causing the surface to become sticky, reducing the scratch resistance of the material, and also producing volatile organic compounds. The addition of ultrafine particle fillers to the resin can improve the mechanical properties of the material, such as increasing the modulus, yield stress and elongation at break, thereby improving the scratch resistance of the material. However, with the increase of filler content, the stress whitening phenomenon caused by scratch damage on the material surface becomes more and more obvious. This is because the filler particles will detach from the resin matrix under strong stress, thereby seriously damaging the surface of the material. Multi-phase and multi-component polymer materials improve the toughness of polymer materials by adding fillers such as rubber. The more polymer material components are added, the stronger the scratch resistance of the polymer material will be, which will reduce scratches accordingly. According to the properties of different polymer materials, the blending components and blending principles can be used to enhance the scratch resistance of multi-phase and multi-component polymer materials and reduce the degree of scratch damage during scratching.

[0004] Chinese patent application No. 202111277133.X discloses a high-toughness scratch-resistant polypropylene and its preparation method and application. The high-toughness scratch-resistant polypropylene of the invention includes the following components calculated by weight: 45-91 parts of polypropylene; 4-30 parts of toughening agent; 0.2-0.5 parts of scratch-resistant agent; 5-25 parts of filler; 0-0.4 parts of lubricant; 0-0.4 parts of antioxidant; wherein the toughening agent includes two components A and B, component A is a combination of one or two of metallocene linear low-density polyethylene or metallocene ethylene-propylene copolymer; component B is POE; the weight ratio of component A to component B is 0.7-3:1. The present invention selects a specific combination of toughening agents to toughen and modify the polypropylene material, and at the same time cooperates with the scratch-resistant agent. When a small amount of scratch-resistant agent is added, the toughness and scratch resistance of polypropylene can be significantly improved at the same time, and the scratch resistance can reach the level of △L<0.5. However, the amide anti-scratch agent or silicone anti-scratch agent used in this invention will precipitate during subsequent use, which may cause the scratch resistance of polypropylene materials to decrease after long-term use. Chinese patent application No. 201810095087.3 discloses the use of metallocene polyolefin elastomer to improve the scratch resistance of the material, but the metallocene polyolefin elastomer needs to be cross-linked to form a cross-linked network to further improve the scratch resistance of the material, and the formation of the cross-linked network will have a certain negative impact on the mechanical properties of the material.

[0005] Therefore, there is still a need in the art to develop a polyethylene protective film with good scratch resistance and long-lasting scratch resistance. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a scratch-resistant PE protective film and a preparation method thereof, wherein the PE protective film has good mechanical properties, excellent scratch resistance and long-lasting scratch resistance, and the preparation process is simple and easy to industrialize.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A scratch-resistant PE protective film comprises the following raw materials, measured by weight: 90-100 parts of LLDPE, 10-20 parts of HDPE, 4-8 parts of TPU, 10-20 parts of modified composite filler, 2-6 parts of modified carbon fiber powder, 0.1-0.3 parts of anti-blocking agent, 0.2-0.4 parts of ultraviolet absorber, and 0.5-1 parts of heat stabilizer.

[0009] Preferably, a scratch-resistant PE protective film comprises the following raw materials, by weight: 95 parts of LLDPE, 15 parts of HDPE, 6 parts of TPU, 15 parts of modified composite filler, 4 parts of modified carbon fiber powder, 0.2 parts of anti-blocking agent, 0.3 parts of ultraviolet absorber, and 0.7 parts of heat stabilizer.

[0010] Preferably, the opening agent is oleamide, the ultraviolet absorber is one or more of UV531, UV327, and UV5411; and the heat stabilizer is one or both of zinc stearate and calcium stearate.

[0011] Preferably, the method for preparing the modified composite filler comprises the following steps:

[0012] (1) adding talcum powder and silicon carbide to anhydrous ethanol, and then adding vinyl triethoxysilane, heating to react, filtering and drying after the reaction is completed, to obtain a modified composite powder;

[0013] (2) adding γ-aminopropyltriethoxysilane to toluene, followed by adding succinic anhydride, stirring at room temperature for 3-4 hours, then adding silica and deionized water, stirring and reacting, filtering, washing, and drying after the reaction is completed to obtain carboxylated silica; then adding the carboxylated silica to anhydrous ethanol, continuing to add glycidyl methacrylate and triphenylphosphine, reacting at 60-70° C. for 2-4 hours, filtering, washing, and drying after the reaction is completed to obtain modified silica;

[0014] (3) adding the modified composite powder in step (1) and the modified silicon dioxide in step (2) into anhydrous ethanol, and then adding trimethylolpropane tris(3-mercaptopropionate) and azobisisobutyronitrile to carry out a constant temperature reaction, filtering, drying, and ball milling to obtain the modified composite filler.

[0015] Preferably, in step (1), the mass ratio of talc, silicon carbide and vinyl triethoxysilane is 50:30-40:5-10, the temperature of the heating reaction is 50-60° C., and the reaction time is 3-4 h.

[0016] Preferably, in step (2), the mass ratio of γ-aminopropyltriethoxysilane, succinic anhydride, silica and deionized water is 20-25:10-12:50-60:100, the stirring reaction temperature is 80-90°C, and the reaction time is 2-3h; the mass ratio of carboxylated silica, glycidyl methacrylate and triphenylphosphine is 20:5-10:0.2-0.3.

[0017] Preferably, in step (3), the mass ratio of the modified composite powder, modified silicon dioxide, trimethylolpropane tris(3-mercaptopropionate) and azobisisobutyronitrile is 20:15-25:5-10:0.1-0.2, the temperature of the isothermal reaction is 55-65° C., and the reaction time is 3-5 h.

[0018] Preferably, the preparation method of the modified carbon fiber is as follows: add 10g of carbon fiber powder to 300mL of anhydrous ethanol, then add 0.3-0.5g of tridecafluorooctyltriethoxysilane, react at 50-60°C for 2-3h, filter and dry after the reaction is completed to obtain the modified carbon fiber powder.

[0019] The present invention also protects a method for preparing the scratch-resistant PE protective film, comprising the following steps:

[0020] S1. Add LLDPE, HDPE, TPU, modified composite filler, modified carbon fiber powder, anti-blocking agent, ultraviolet absorber and heat stabilizer into a high-speed mixer and mix them evenly according to the formula, then add them into a twin-screw extruder for extrusion granulation, and then dry them to obtain polyethylene masterbatch;

[0021] S2. Adding the polyethylene masterbatch obtained in step S1 into a blow molding machine, and preparing the scratch-resistant PE protective film through a film blowing process.

[0022] Preferably, the temperature of the extrusion granulation in step S1 is 190-230°C; the film blowing process in step S2 is: the temperature of zone 1 is 100-120°C, the temperature of zone 2 is 140-160°C, the temperature of zone 3 is 150-180°C, the temperature of zone 4 is 180-220°C, the temperature of zone 5 is 200-210°C, the die head temperature is 190-200°C, the blowing ratio is 1.5-2.2, and the drawing ratio is 1.8-2.6.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The scratch-resistant PE protective film provided by the present invention takes LLDPE as the base material and adds HDPE and TPU to blend it. On the one hand, the toughness and strength of the LLDPE material can be improved, and the scratch resistance of the PE protective film can be improved. On the other hand, HDPE and TPU have good wear resistance, which can effectively reduce the wear degree of the PE film surface and improve the long-term scratch resistance of the PE protective film.

[0025] (2) The scratch-resistant PE protective film provided by the present invention includes a modified composite filler, wherein talcum powder and silicon carbide are first mixed and modified to introduce double bonds on the surface of the talcum powder, which is beneficial to the subsequent reaction. Meanwhile, the added vinyl triethoxysilane can also improve the compatibility between talcum powder, silicon carbide and polyethylene, and improve the mechanical properties of the PE protective film. In addition, talcum powder has high slipperiness, which reduces the surface friction coefficient of the PE protective film. Silicon carbide has high hardness, which improves the wear resistance of the PE protective film. The synergistic effect of the two improves the scratch resistance of the PE protective film. Subsequently, the nano-silicon dioxide is carboxylated and then reacted with glycidyl methacrylate to introduce organic small molecules containing double bonds on the surface of the silicon dioxide. Finally, the modified The composite powder and modified silicon dioxide react together, and under the action of trimethylolpropane tris(3-mercaptopropionate), a mercapto-ene reaction is carried out, so that the three inorganic particles are combined in the form of chemical bonds. The addition of silicon dioxide further improves the wear resistance of the composite filler, and the surfaces of the three inorganic particles are coated with long-chain organic small molecules, which improves the interfacial bonding force of the composite filler in the PE protective film matrix, thereby improving the long-lasting scratch resistance of the PE protective film; the added modified carbon fiber powder reacts with tridecafluorooctyl triethoxysilane, so that fluorine-containing long-chain silane is introduced into the surface of the carbon fiber, and fluorine silicon groups are introduced, so that the PE film material has a lower surface energy and surface friction coefficient, so that the surface scratch resistance is further improved.

[0026] (3) The scratch-resistant PE protective film provided by the present invention is filled with inorganic particles and other wear-resistant polymer materials are introduced. Under the synergistic effect of various components, the scratch resistance of the PE protective film is significantly improved. At the same time, the inorganic particles are modified to improve their compatibility with the polymer, thereby making the PE protective film have good mechanical properties and long-lasting scratch resistance, and has good application prospects. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The brand of LLDPE is Sinopec DFDA-7042; the brand of HDPE is Borealis HE2558; the brand of TPU is BASF ES85A15000; the talcum powder is purchased from Yuyao Jushi New Materials Co., Ltd., with a mesh size of 2000 mesh; the silicon carbide is purchased from Anyang Zhongxing Refractory Materials Co., Ltd., with a mesh size of 2500 mesh; the silicon dioxide is purchased from Jinan DeLan Chemical Co., Ltd., with a particle size of 900nm; the carbon fiber powder is purchased from Jiangxi Shuobang New Materials Technology Co., Ltd., with a mesh size of 2000 mesh.

[0029] Example 1

[0030] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0031] S1. According to the formula, 950g LLDPE, 150g HDPE, 60g TPU, 150g modified composite filler, 40g modified carbon fiber powder, 2g oleic acid amide, 3g UV5411, and 7g calcium stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 220° C., followed by drying to obtain polyethylene masterbatch;

[0032] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 110°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 170°C, the temperature of zone 4 is 210°C, the temperature of zone 5 is 200°C, the die head temperature is 200°C, the blowing ratio is 1.8, and the draft ratio is 2.4.

[0033] The method for preparing the modified composite filler comprises the following steps:

[0034] (1) 50 g of talc and 35 g of silicon carbide were added to 800 mL of anhydrous ethanol, followed by the addition of 8 g of vinyltriethoxysilane, and the mixture was reacted at 55° C. for 3.5 h. After the reaction was completed, the mixture was filtered and dried to obtain a modified composite powder;

[0035] (2) 25 g of γ-aminopropyltriethoxysilane was added to 900 mL of toluene, followed by 12 g of succinic anhydride, and stirred at room temperature for 2.5 h. Subsequently, 55 g of silica and 100 g of deionized water were added, and the mixture was stirred and reacted at 85° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain carboxylated silica. Then, 20 g of carboxylated silica was added to 500 mL of anhydrous ethanol, and 8 g of glycidyl methacrylate and 0.25 g of triphenylphosphine were added, and the mixture was reacted at 65° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified silica.

[0036] (3) Add 20 g of the modified composite powder in step (1) and 20 g of the modified silica in step (2) to 600 mL of anhydrous ethanol, then add 8 g of trimethylolpropane tris(3-mercaptopropionate) and 0.15 g of azobisisobutyronitrile, and react at 60° C. for 4 h. After completion, filter, dry, and ball-mill to obtain the modified composite filler.

[0037] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.4 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 55° C. for 2.5 hours. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0038] Example 2

[0039] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0040] S1. According to the formula, 950g LLDPE, 150g HDPE, 50g TPU, 150g modified composite filler, 40g modified carbon fiber powder, 2g oleic acid amide, 3g UV531, and 7g zinc stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 210° C., followed by drying to obtain polyethylene masterbatch;

[0041] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 110°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 160°C, the temperature of zone 4 is 210°C, the temperature of zone 5 is 200°C, the die head temperature is 190°C, the blowing ratio is 1.7, and the drawing ratio is 2.2.

[0042] The method for preparing the modified composite filler comprises the following steps:

[0043] (1) 50 g of talc and 35 g of silicon carbide were added to 800 mL of anhydrous ethanol, followed by the addition of 7 g of vinyltriethoxysilane, and the mixture was reacted at 55° C. for 3.5 h. After the reaction was completed, the mixture was filtered and dried to obtain a modified composite powder;

[0044] (2) 23 g of γ-aminopropyltriethoxysilane was added to 900 mL of toluene, followed by 11 g of succinic anhydride, and stirred at room temperature for 3.5 h. Subsequently, 55 g of silica and 100 g of deionized water were added, and the mixture was stirred and reacted at 85° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain carboxylated silica. Then, 20 g of carboxylated silica was added to 500 mL of anhydrous ethanol, and 8 g of glycidyl methacrylate and 0.2 g of triphenylphosphine were added, and the mixture was reacted at 65° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified silica.

[0045] (3) Add 20 g of the modified composite powder in step (1) and 20 g of the modified silica in step (2) to 600 mL of anhydrous ethanol, then add 7 g of trimethylolpropane tris(3-mercaptopropionate) and 0.1 g of azobisisobutyronitrile, and react at 60° C. for 4 h. After completion, filter, dry, and ball-mill to obtain the modified composite filler.

[0046] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.4 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 55° C. for 3 h. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0047] Example 3

[0048] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0049] S1. According to the formula, 900 g LLDPE, 100 g HDPE, 40 g TPU, 100 g modified composite filler, 20 g modified carbon fiber powder, 1 g oleamide, 2 g UV327, and 5 g zinc stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 190° C., followed by drying to obtain polyethylene masterbatch;

[0050] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 100°C, the temperature of zone 2 is 140°C, the temperature of zone 3 is 150°C, the temperature of zone 4 is 180°C, the temperature of zone 5 is 200°C, the die head temperature is 190°C, the blowing ratio is 1.5, and the drawing ratio is 1.8.

[0051] The method for preparing the modified composite filler comprises the following steps:

[0052] (1) 50 g of talc and 30 g of silicon carbide were added to 800 mL of anhydrous ethanol, followed by the addition of 5 g of vinyltriethoxysilane, and the mixture was reacted at 50 °C for 4 h. After the reaction was completed, the mixture was filtered and dried to obtain a modified composite powder;

[0053] (2) 20 g of γ-aminopropyltriethoxysilane was added to 900 mL of toluene, followed by 10 g of succinic anhydride, and stirred at room temperature for 3 h. Subsequently, 50 g of silica and 100 g of deionized water were added, and the mixture was stirred and reacted at 80° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain carboxylated silica. Then, 20 g of carboxylated silica was added to 500 mL of anhydrous ethanol, and 5 g of glycidyl methacrylate and 0.2 g of triphenylphosphine were added, and the mixture was reacted at 60° C. for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified silica.

[0054] (3) Add 20 g of the modified composite powder in step (1) and 15 g of the modified silica in step (2) to 600 mL of anhydrous ethanol, then add 5 g of trimethylolpropane tris(3-mercaptopropionate) and 0.1 g of azobisisobutyronitrile, and react at 55° C. for 5 h. After completion, filter, dry, and ball-mill to obtain the modified composite filler.

[0055] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.3 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 50° C. for 3 h. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0056] Example 4

[0057] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0058] S1. According to the formula, 1000g LLDPE, 200g HDPE, 80g TPU, 200g modified composite filler, 60g modified carbon fiber powder, 3g oleic acid amide, 4g UV5411, and 10g calcium stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 230° C., followed by drying to obtain polyethylene masterbatch;

[0059] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 120°C, the temperature of zone 2 is 160°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 220°C, the temperature of zone 5 is 210°C, the die head temperature is 200°C, the blowing ratio is 2.2, and the draft ratio is 2.6.

[0060] The method for preparing the modified composite filler comprises the following steps:

[0061] (1) 50 g of talc and 40 g of silicon carbide were added to 800 mL of anhydrous ethanol, followed by the addition of 10 g of vinyltriethoxysilane, and the mixture was reacted at 60 ° C for 3 h. After the reaction was completed, the mixture was filtered and dried to obtain a modified composite powder;

[0062] (2) 25 g of γ-aminopropyltriethoxysilane was added to 900 mL of toluene, followed by 12 g of succinic anhydride, and stirred at room temperature for 4 h. Subsequently, 60 g of silica and 100 g of deionized water were added, and the mixture was stirred and reacted at 90° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain carboxylated silica. Then, 20 g of carboxylated silica was added to 500 mL of anhydrous ethanol, and 10 g of glycidyl methacrylate and 0.3 g of triphenylphosphine were added, and the mixture was reacted at 70° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified silica.

[0063] (3) Add 20 g of the modified composite powder in step (1) and 25 g of the modified silica in step (2) to 600 mL of anhydrous ethanol, then add 10 g of trimethylolpropane tris(3-mercaptopropionate) and 0.2 g of azobisisobutyronitrile, and react at 65° C. for 3 h. After completion, filter, dry, and ball-mill to obtain the modified composite filler.

[0064] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.5 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 60° C. for 3 h. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0065] Comparative Example 1

[0066] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0067] S1. According to the formula, 950g LLDPE, 150g HDPE, 60g TPU, 150g modified composite filler, 40g modified carbon fiber powder, 2g oleic acid amide, 3g UV5411, and 7g calcium stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 220° C., followed by drying to obtain polyethylene masterbatch;

[0068] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 110°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 170°C, the temperature of zone 4 is 210°C, the temperature of zone 5 is 200°C, the die head temperature is 200°C, the blowing ratio is 1.8, and the draft ratio is 2.4.

[0069] The method for preparing the modified composite filler comprises the following steps:

[0070] (1) 50 g of talc and 35 g of silicon carbide were added to 800 mL of anhydrous ethanol, followed by the addition of 8 g of vinyltriethoxysilane, and the mixture was reacted at 55° C. for 3.5 h. After the reaction was completed, the mixture was filtered and dried to obtain a modified composite powder;

[0071] (2) 25 g of γ-aminopropyltriethoxysilane was added to 900 mL of toluene, followed by 12 g of succinic anhydride, and stirred at room temperature for 2.5 h. Subsequently, 55 g of silica and 100 g of deionized water were added, and the mixture was stirred and reacted at 85° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain carboxylated silica. Then, 20 g of carboxylated silica was added to 500 mL of anhydrous ethanol, and 8 g of glycidyl methacrylate and 0.25 g of triphenylphosphine were added, and the mixture was reacted at 65° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified silica.

[0072] (3) 20 g of the modified composite powder in step (1) and 20 g of the modified dioxygen in step (2) are mixed evenly to obtain the modified composite filler.

[0073] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.4 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 55° C. for 2.5 hours. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0074] Comparative Example 2

[0075] A method for preparing a scratch-resistant PE protective film comprises the following steps:

[0076] S1. According to the formula, 950g LLDPE, 150g HDPE, 60g TPU, 150g modified composite filler, 40g modified carbon fiber powder, 2g oleic acid amide, 3g UV5411, and 7g calcium stearate were added into a high-speed mixer and mixed evenly, and then added into a twin-screw extruder for extrusion granulation at a granulation temperature of 220° C., followed by drying to obtain polyethylene masterbatch;

[0077] S2. Add the polyethylene masterbatch obtained in step S1 into a blow molding machine, and prepare the scratch-resistant PE protective film by a film blowing process, wherein the film blowing process is as follows: the temperature of zone 1 is 110°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 170°C, the temperature of zone 4 is 210°C, the temperature of zone 5 is 200°C, the die head temperature is 200°C, the blowing ratio is 1.8, and the draft ratio is 2.4.

[0078] The method for preparing the modified composite filler comprises the following steps:

[0079] (1) 50 g of talcum powder and 35 g of silicon carbide were mixed uniformly to obtain a composite powder;

[0080] (2) Add 20 g of the composite powder in step (1) and 20 g of silicon dioxide in step (2) to 600 mL of anhydrous ethanol, then add 8 g of trimethylolpropane tris(3-mercaptopropionate) and 0.15 g of azobisisobutyronitrile, and react at 60° C. for 4 h. After completion, filter, dry, and ball-mill to obtain the modified composite filler.

[0081] The preparation method of the modified carbon fiber is as follows: 10 g of carbon fiber powder is added to 300 mL of anhydrous ethanol, and then 0.4 g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 55° C. for 2.5 hours. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

[0082] The scratch-resistant polyethylene masterbatch prepared in Examples 1-4 and Comparative Examples 1-2 was pressed into standard samples for scratch resistance test. The scratch resistance was tested according to the method in Volkswagen's standard PV3952 "Plastic Interior Parts Scratch Resistance Test". The test parameters were: load 10N, speed 1000mm / min, spacing 2mm, and scratch length 40mm. A spectrophotometer was used to subtract the L value before scratching from the L value measured after scratching (L represents lightness and darkness, reflecting the depth of color) to obtain the lightness difference (ΔL) of the surface scratch. The smaller the ΔL value of the test result, the better the scratch resistance. The double 85 test was an accelerated precipitation aging test. The test conditions were 180 days of treatment at 85°C and 85% relative humidity. After the test, the sample was taken out, the sample surface was wiped dry with absorbent cotton, and the sample was placed at 25°C and 50% relative humidity for 23 hours for testing. The test results are shown in Table 1 below:

[0083] Table 1

[0084] Scratch resistance ΔL Scratch resistance after double 85 test ΔL Example 1 0.98 1.06 Example 2 1.02 1.10 Example 3 1.09 1.15 Example 4 0.87 0.96 Comparative Example 1 1.42 1.93 Comparative Example 2 1.96 2.55

[0085] The scratch-resistant PE protective films prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, and the tensile strength and elongation at break were tested according to standard GB / T 1040.1-2018. The specimen was a type 2 specimen with a width of 20 mm, a length of 250 mm, a thickness of 100 μm, and a tensile speed of 20 mm / min. The test results are shown in Table 2 below:

[0086] Table 2

[0087]

[0088] It can be seen from Tables 1-2 above that the scratch-resistant PE protective film prepared by the present invention, the addition of modified composite fillers, not only makes the PE film have good scratch resistance and long-lasting scratch resistance, but also has good mechanical properties and has good application prospects.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A scratch-resistant PE protective film, characterized in that: The raw materials are as follows, calculated by weight: 90-100 parts of LLDPE, 10-20 parts of HDPE, 4-8 parts of TPU, 10-20 parts of modified composite filler, 2-6 parts of modified carbon fiber powder, 0.1-0.3 parts of opening agent, 0.2-0.4 parts of ultraviolet absorber and 0.5-1 parts of heat stabilizer.

2. The scratch-resistant PE protective film according to claim 1, characterized in that: The following raw materials are included by weight: 95 parts of LLDPE, 15 parts of HDPE, 6 parts of TPU, 15 parts of modified composite filler, 4 parts of modified carbon fiber powder, 0.2 parts of opening agent, 0.3 parts of ultraviolet absorber and 0.7 parts of heat stabilizer.

3. The scratch-resistant PE protective film according to claim 1, characterized in that: The opening agent is oleic acid amide, the ultraviolet absorber is one or more of UV531, UV327, and UV5411; and the heat stabilizer is one or two of zinc stearate and calcium stearate.

4. The scratch-resistant PE protective film according to claim 1, characterized in that: The preparation method of the modified composite filler comprises the following steps: (1) adding talcum powder and silicon carbide to anhydrous ethanol, and then adding vinyl triethoxysilane, heating to react, filtering and drying after the reaction is completed to obtain a modified composite powder; (2) Add γ-aminopropyltriethoxysilane to toluene, then add succinic anhydride, stir at room temperature for 3-4 hours, then add silica and deionized water, stir and react, filter, wash and dry after the reaction is completed to obtain carboxylated silica; then add carboxylated silica to anhydrous ethanol, continue to add glycidyl methacrylate and triphenylphosphine, react at 60-70°C for 2-4 hours, filter, wash and dry after the reaction is completed to obtain modified silica; (3) Add the modified composite powder in step (1) and the modified silicon dioxide in step (2) into anhydrous ethanol, and then add trimethylolpropane tris(3-mercaptopropionate) and azobisisobutyronitrile to carry out a constant temperature reaction. After completion, filter, dry, and ball mill to obtain the modified composite filler.

5. The scratch-resistant PE protective film according to claim 4, characterized in that: In step (1), the mass ratio of talc, silicon carbide and vinyl triethoxysilane is 50:30-40:5-10, the temperature of the heating reaction is 50-60° C., and the reaction time is 3-4 hours.

6. The scratch-resistant PE protective film according to claim 4, characterized in that: In step (2), the mass ratio of γ-aminopropyltriethoxysilane, succinic anhydride, silica and deionized water is 20-25:10-12:50-60:100, the stirring reaction temperature is 80-90°C, and the reaction time is 2-3h; the mass ratio of carboxylated silica, glycidyl methacrylate and triphenylphosphine is 20:5-10:0.2-0.

3.

7. The scratch-resistant PE protective film according to claim 4, characterized in that: In step (3), the mass ratio of the modified composite powder, modified silicon dioxide, trimethylolpropane tris(3-mercaptopropionate) and azobisisobutyronitrile is 20:15-25:5-10:0.1-0.2, the temperature of the isothermal reaction is 55-65° C., and the reaction time is 3-5 h.

8. The scratch-resistant PE protective film according to claim 1, characterized in that: The preparation method of the modified carbon fiber is as follows: 10g of carbon fiber powder is added to 300mL of anhydrous ethanol, and then 0.3-0.5g of tridecafluorooctyltriethoxysilane is added, and the mixture is reacted at 50-60°C for 2-3h. After the reaction is completed, the mixture is filtered and dried to obtain the modified carbon fiber powder.

9. A method for preparing the scratch-resistant PE protective film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add LLDPE, HDPE, TPU, modified composite filler, modified carbon fiber powder, anti-blocking agent, ultraviolet absorber and heat stabilizer into a high-speed mixer and mix them evenly according to the formula, then add them into a twin-screw extruder for extrusion granulation, and then dry them to obtain polyethylene masterbatch; S2. Adding the polyethylene masterbatch obtained in step S1 into a blow molding machine, and preparing the scratch-resistant PE protective film through a film blowing process.

10. The preparation method according to claim 9, characterized in that: The temperature of the extrusion granulation in step S1 is 190-230°C; the film blowing process in step S2 is: the temperature of zone 1 is 100-120°C, the temperature of zone 2 is 140-160°C, the temperature of zone 3 is 150-180°C, the temperature of zone 4 is 180-220°C, the temperature of zone 5 is 200-210°C, the die head temperature is 190-200°C, the blowing ratio is 1.5-2.2, and the draft ratio is 1.8-2.6.

Citation Information

Patent Citations

  • Silver-texture spraying-free composite and preparation method and application thereof

    CN106496773A

  • Scratch-resistant high-performance photodiffusion PC material and preparation method thereof

    CN110240792A

  • Low-emission scratch-resistant modified polypropylene as well as preparation method and application thereof

    CN111234387A

  • Scratch-resistant modified PP material and preparation method thereof

    CN111793273A

  • Cable protection pipe

    CN116355316A